The Perencanaan Pembelajaran Pendidikan Anak Usia Dini dalam Meningkatkan Kompetensi Pedagogik Guru dengan Menggunakan Artifisial Intelegensi - Deden Deni Mahendra; Ayi Najmul Hidayat (EduInovasi: Journal of Basic Educational Studies, 2026)
Early childhood education plays a strategic role in establishing the foundation for long-term development, making the quality of learning planning a crucial factor in determining the effectiveness of the learning process. This study aims to describe how early childhood education (PAUD) learning planning can improve teachers' pedagogical competence through the use of Artificial Intelligence (AI) in Rengasdengklok District. This research method uses a descriptive qualitative approach to explore the practice of AI-based learning planning in depth, with a descriptive study involving PAUD teachers as the main subjects. The results show that the use of AI helps teachers develop more systematic, adaptive, and developmentally appropriate learning plans. Teachers utilize AI applications and tools to identify student characteristics, design varied learning strategies, and develop more structured daily plans. The use of AI also strengthens teachers' ability to organize materials and select learning methods appropriate to the classroom context. Furthermore, AI integration has been shown to encourage teachers to be more reflective in the planning process through more accurate data analysis. The implications of this study emphasize the importance of improving PAUD teachers' digital literacy and institutional support in providing adequate technological devices.